Effects of ABC Running and Bodyweight Training combination: A case study on the speed of hurdling athletes [Efectos de la combinacin ABC Running y Bodyweight Training: Un estudio de caso sobre la velocidad de los atletas de vallas] - Jaffry bin Zakaria (Tanjung Malim, 2024)
Effects of ABC Running and Bodyweight Training combination: A case study on the speed of hurdling athletes [Efectos de la combinacin ABC Running y Bodyweight Training: Un estudio de caso sobre la velocidad de los atletas de vallas] by Jaffry bin Zakaria